Vous êtes sur la page 1sur 1

FORMULAS DE INTEGRACION

DERIVACION POR MEDIO DE FORMULAS

1.
∫ dx = x + c , c =constante 23. du 1 u
= arctg + c
1. d (c ) = 0 2.d ( x n ) = nx n−1 3. d (c f ) = c df
2. n u n +1 ∫u 2
+a 2
a a
4. d (u n ) = n u n−1 du 5. d (a u ) = a u . ln a.du ⇒ ( si a = e) : d (e u ) = e u . du ∫ u du = n + 1 + c, n ≠ −1
d 3. du 1 u−a
6. 7. d ( u ) = v du − u dv ∫ cf ( x)dx = c∫ f ( x) dx 24. = Ln +c
dx
(uv ) = u dv + v du
dx v v2
∫u −a 22
2a u+a
4.
8.
d 1 d 1 ∫ (u + v)dx = ∫ udx + ∫ v. dx du 1 a+u
(loga u ) = . log a e. du ⇒ ( si a = e ) : ( Ln u ) = du 25.
dx u dx u 5. u au a>0 ∫ a 2 − u 2 = 2a Ln a − u + c
9. d ( sen u ) = cos u. du 10. d (cos u ) = − sen u. du ∫ a .du = Ln a
+ c,
a ≠1 du u
26.
11. d (tan u ) = sec 2 u. du 12. (c tan u ) = − csc 2 u. du 6. u
∫ e .du = e
u
+c ∫ a 2 − u 2 = arcsen a + c
13. d (sec u ) = sec u . tan u. du 14. d (csc u ) = − csc u . c tan u. du 7. du
27.
∫ sen u.du = − cos u + c ∫ = Ln u + u 2 − a 2 + c
15. d ( arc sen u ) = du 16. d
(arc cos u ) =
− du u −a2 2
8.
dx 1 − u2 dx 1 − u2 ∫ ln u du = u ln u − u 28. du
9. ∫ = Ln u + u 2 + a 2 + c
17. d
(arc tan u ) =
du 18. d ( arc c tan u ) = − du ∫ cos u.du = sen u + c u +a2 2

dx 1 + u2 dx 1 + u2 10. du 1 u
∫ tg u . du = − Ln cos u + c 29.
∫u = arc sec + c
19. d du 20. d ( arc csc u ) = − du 11. u −a2 2 a a
dx
(arc sec u ) =
u u2 − 1 dx u u2 − 1
∫ ctg u . du = Ln sen u + c ⎛ a + u2 + a2 ⎞
30. du1
' g ( x) '
12.
∫ sec u . du = Ln sec u + tg u ∫ u a 2 + u 2 a ⎜⎜ Ln =−
u
⎟+c

21. Si y = u v ⇒ Ln y = v. Lnu 22. g ( x) = g ( x) 13.
⎝ ⎠
g ( x) ∫ csc u . du = Ln csc u − ctg u 31. du 1 ⎛ 2
a+ a −u ⎟ 2 ⎞

23. d ( f ! g )( x) = f ʹ( g ( x)). g ʹ( x) 14. 2


∫ sec u . du = tg u + c ∫ u a 2 − u 2 = − a Ln ⎜⎜ u ⎟
+c
⎝ ⎠
15. 2
1. sen 2 A = 2sen A. cos A 2. cos 2 A = cos 2 A − sen 2 A = 1 − 2 sen 2 A ∫ csc u . du = −ctg u + c 32. a 2 − u 2 du =
1 1
u a 2 − u 2 + a 2 .arcsen
u
16.
∫ 2 2 a
3. tg 2 A =
2 tg A 1
4. sen 2 x = (1 − cos 2 x) ∫ sec u . tg u . du = sec u + c 33. 1 1
1 − tg 2 A 2 17. ∫ u 2 ± a 2 du = u u 2 ± a 2 ± a 2 Ln u + u 2 ± a 2
1 ∫ csc u . ctg u . du = − csc u + c 2 2
5. cos 2 x = (1 + cos 2 x) 6. sen( A ± B) = senA. cos B ± cos A. senB u sen 2u
2 18. 2
∫ sen u. du = 2 − 4 + c 1 + ctg 2θ = csc2 θ
7. cos( A ± B) = cos A. cos B ! senA. senB tg A ± tg B u sen 2u 1 + tg 2θ = sec 2 θ
8. tg ( A ± B) = 19. 2
1 ! tgA.tgB ∫ cos u. du =
2
+
4
+c
⎛ A± B⎞ ⎛ A! B⎞ ⎛ A + B⎞ ⎛ A −B⎞ 20. 2 I) a 2 − x 2 ⇒ x = a sen t
9. senA ± senB = 2sen⎜ ⎟ cos⎜
⎝ 2 ⎠ ⎝ 2 ⎠
⎟ 10. cos A + cos B = 2 cos⎜ ⎟ cos⎜
⎝ 2 ⎠ ⎝ 2 ⎠
⎟ ∫ tg u. du =(tgu − u) + c
21. 2 II) x 2 − a 2 ⇒ x = a sec t
∫ ctg u. du = (−ctg u − u) + c
⎛ A+ B⎞ ⎛ A− B⎞ 1 du III) x 2 + a 2 ⇒ x = a tg t
11. cos A − cos B = −2sen⎜ ⎟ sen⎜ ⎟ 12. senA . cos B = [sen( A + B ) + sen( A − B )] 22.
⎝ 2 ⎠ ⎝ 2 ⎠ 2 ∫ u = Ln u + Ln c = Ln (cu )
1 1
13. senA . senB = [cos(A − B ) − cos( A + B )] 14. cos A . cos B = [cos(A + B ) + cos(A − B )]
2 2